Assessment of Ethnicity in Indian Population using Tooth Crown Metric Dental Traits - Deepak, V (J Int Oral Health, 2015)
BACKGROUND: Tooth crown dimensions vary between different ethnic groups, providing insights into the factors controlling human dental development. This present study compares permanent mesiodistal (MD) and buccolingual crown dimensions between four ethnic groups, highlighting patterns of tooth size between these groups and considers the findings in relation to genetic and environmental influences. MATERIALS AND METHODS: MD and buccolingual tooth crown dimensions were recorded using digital vernier calipers on dental casts derived from four different human population: Iranians, Hindus, Muslims, and Christians. RESULTS: Obtained measurements were subjected to statistical analysis. The Christian sample was found to have the largest teeth overall, whereas the Iranian sample generally displayed the smallest MD and buccolingual crown dimensions (P < 0.001). Comparisons of coefficients of variation for teeth within each class showed that the later-forming teeth displayed greater variation in MD size than the earlier-forming teeth. CONCLUSION: The different patterns of tooth size observed between the study samples are thought to reflect differences in the relative contributions of genetic and environmental influences to dental development between the four population. Using a standardized methodology, significant differences in MD and buccolingual crown dimensions have been demonstrated between four human ethnic groups. There were also distinct differences in the patterns of crown size between the groups, with the later-forming teeth in each type generally showing greater size variation.